Simulation of center location of fluid flow in shear driven cavity using lattice Boltzmann method - Wan Mohd Hanif, Othman (2012)
The study of center location of lid driven cavity using lattice Boltzmann method is all about the of the fluid dynamic base on the simulation and prediction the flow. The study is base on steady flow and transient flow using Lattice Boltzmann method to understant the capability of Lattice Boltzmann. The simulation of Lattice Boltzmann is using FOTRAN software. The result is compare with Ghia et al to validate the stream function is in good arrangement and also can determine the capability of LBM. The result have been compare with simulation lid driven cavity using ANSYS(FLUENT) using navier stoke solver at the transient flow in Reynolds number 100 to 10000. From the simulation, the lattice Boltzmann method is capable at Reynolds number below than 7500.